2020
DOI: 10.21203/rs.3.rs-25164/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of changes in blood urea and creatinine levels in patients with coronavirus disease 2019 (COVID-19)

Abstract: Background Coronavirus disease 2019 (COVID-19) is new respiratory tract infections disease with an evolving understanding of its epidemiology and clinical appearances. Kidney defect seems to be common in patients with Covid-19. Urea and creatinine level often occurs at the beginning or during the infection. This evidence shows that Covid-19 also attacks the kidneys. The aim of this study was to evaluate changes in biochemical parameters associated with kidney function, including urea and creatinine in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…The summary of characteristics extracted from studies is presented in Table 1. From 22 included studies, 9 were cohort (17,(19)(20)(21)(23)(24)(25)33,36), 8 were cross-sectional (26,(30)(31)(32)34,35,37,38), one was case-control (28), and 4 were trials (18,22,27,29). Nineteen studies had completed peer-review processes and were published from June to November 2020; while three studies (21,24,32) were not granted publication and peer-review at the time of inclusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The summary of characteristics extracted from studies is presented in Table 1. From 22 included studies, 9 were cohort (17,(19)(20)(21)(23)(24)(25)33,36), 8 were cross-sectional (26,(30)(31)(32)34,35,37,38), one was case-control (28), and 4 were trials (18,22,27,29). Nineteen studies had completed peer-review processes and were published from June to November 2020; while three studies (21,24,32) were not granted publication and peer-review at the time of inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…The studies provided a perfect geographical distribution. While 12 articles reported results from more than 7 hospitals located in various districts of Tehran, Iran's capital and the most populous city (17-20, 23,26,27,30,33,34,36,37), other studies were carried out in Zahedan (the Southeast) (21,35), Abadan (the Southwest) ( 22), Qom (the center) (24), Urmia and Tabriz (the northwest) (25,29,31), Mazandaran and Rasht (the north) (28,38), and Nahavand (the west) (32). Three studies were conducted in a multi-center fashion (21,25,30), (17,20,23,24,27,36,38) which is an increase in serum creatinine by 0.3 mg/ dL within 48 hours or a 50% increase in serum creatinine from baseline within 7 days (39).…”
Section: Resultsmentioning
confidence: 99%
“…Increased urea levels were found to correspond with the severity of COVID-19 infection in a research involving 138 patients by Wang et al [34]. Impaired renal function, according to Mahmoudi et al, is a major cause of death in COVID-19 patients [35]. In research by Li et al [36], urea levels were found to be strongly associated with disease prognosis.…”
Section: The Identification Of Biochemical Indicators Accessible At T...mentioning
confidence: 96%
“…Wu et al discovered that advanced age was associated with a greater fatality rate [43,44]. In a study conducted by Mahmoudi et al, elderly patients with decreased renal function had higher urea and creatinine levels [35]. An intriguing question arises here in that these molecular indicators may become disordered in other serious disorders.…”
Section: The Identification Of Biochemical Indicators Accessible At T...mentioning
confidence: 99%
“…Symptoms of kidney problem include raised levels of protein or blood in the urine. COVID patients with diabetes and high blood pressure increase the risk of kidney disease [19][20][21] . Heart: Patient affected with coronavirus has infected lungs which pump less oxygen to the bloodstreams, The heart, therefore, has to work harder to pump blood which proves to be dangerous in patients with pre-existing heart disease leading to cardiac arrest.…”
Section: Symptomsmentioning
confidence: 99%